2008
DOI: 10.1534/genetics.107.083733
|View full text |Cite
|
Sign up to set email alerts
|

Control of Antagonistic Components of the Hedgehog Signaling Pathway by microRNAs in Drosophila

Abstract: Hedgehog (Hh) signaling is critical for many developmental processes and for the genesis of diverse cancers. Hh signaling comprises a series of negative regulatory steps, from Hh reception to gene transcription output. We previously showed that stability of antagonistic regulatory proteins, including the coreceptor Smoothened (Smo), the kinesin-like Costal-2 (Cos2), and the kinase Fused (Fu), is affected by Hh signaling activation. Here, we show that the level of these three proteins is also regulated by a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
(34 reference statements)
1
35
0
1
Order By: Relevance
“…53 This study showed that multiple transcripts that encode members of a multicomponent cytoplasmic complex in the Hh pathway were directly repressed by miR-12 and/or miR-283, including costal-2, smoothened and fused. These were demonstrated as endogenous targets since imaginal disc cells lacking the miRNA cluster exhibited modestly increased levels of transgenic 3'UTR sensors for these target genes.…”
Section: Observed Roles For Mirnas In Cell Signaling Pathwaysmentioning
confidence: 81%
See 1 more Smart Citation
“…53 This study showed that multiple transcripts that encode members of a multicomponent cytoplasmic complex in the Hh pathway were directly repressed by miR-12 and/or miR-283, including costal-2, smoothened and fused. These were demonstrated as endogenous targets since imaginal disc cells lacking the miRNA cluster exhibited modestly increased levels of transgenic 3'UTR sensors for these target genes.…”
Section: Observed Roles For Mirnas In Cell Signaling Pathwaysmentioning
confidence: 81%
“…Nevertheless, this was insufficient to lead to a phenotypic defect in Hh pathway output in miRNA mutant cells. 53 Possibly the miRNAs are required only for fine-tuning signaling. On the other hand, since Costal-2 and Smoothened are antagonistically-acting components of the Hh pathway, it is conceivable that the miRNA deletion situation represents an intermediate, phenotypically suppressed condition.…”
Section: Observed Roles For Mirnas In Cell Signaling Pathwaysmentioning
confidence: 99%
“…To understand why the costal-2 reporter could be insensitive to GW182 (or Atx2) knockdown, we examined the sequence of its 3′ UTR and found it to contain not only target sites for miR12 and miR283, as reported earlier (38), but also two binding sites for miR277. This finding is significant because, unlike the majority of Dcr1-dependent miRNAs, miR277 is loaded preferentially onto Ago2-RISC complexes because of the extensive basepairing between its miRNA and miRNA* strands (40)(41)(42).…”
Section: Atx2mentioning
confidence: 85%
“…4 B and B′) reporters. Given that the latter two reporters are regulated by artificial UTRs engineered to be repressed solely through the miRNA pathway (37,38), these data strongly argue that Atx2 is broadly required for miRNA function.…”
Section: Atx2mentioning
confidence: 95%
“…It remains to be seen elusive if such a regulatory scheme of a miR-NA family applies to all multi-cell organisms. At least in D. melanogaster, a miRNA cluster is found to impair hedgehog signaling [66].…”
Section: Discussionmentioning
confidence: 99%